2010
DOI: 10.1007/s11664-010-1131-6
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Analysis of Iron Contamination Effect in Multicrystalline Silicon Wafers for Solar Cells

Abstract: We investigated the effect of Fe contamination on the electronic properties of dislocation clusters in relation to oxygen precipitation in multicrystalline silicon (mc-Si). Photoluminescence (PL) spectroscopy and mapping were performed at room and liquid-He temperatures on mc-Si wafers before and after Fe contamination. PL spectra consisted of the band-edge emission, the 0.78-eV emission associated with oxygen precipitates, and the dislocation-related D-lines. The Fe contamination increased the electrically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…3,4 During the last decade, much research effort has been invested into understanding the origins of the D-band emission lines, in particular their relation to various types of dislocations and metal contamination. 5 It has been suggested that D1 and D2 lines originate from the a Electronic mail: espen.olsen@umb.no defects produced by the same dislocation processes, and likewise for D3 and D4 lines. The former and the latter defects are, however, believed to be different from each other in nature.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 During the last decade, much research effort has been invested into understanding the origins of the D-band emission lines, in particular their relation to various types of dislocations and metal contamination. 5 It has been suggested that D1 and D2 lines originate from the a Electronic mail: espen.olsen@umb.no defects produced by the same dislocation processes, and likewise for D3 and D4 lines. The former and the latter defects are, however, believed to be different from each other in nature.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Oxygen is another major impurity in conjunction with iron that may occur at small-angle grain boundaries, deteriorating the minority carrier lifetime. 21,22 In order to improve the characteristics of silicon substrates for solar cells, such intra-grain defects must be reduced. However, clarifying the generation of these defects is difficult because many crystalline defects occur in multi-crystalline silicon.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 It makes measurement of defect concentration, using RTPL, possible. Monitoring of surface defect formation during oxidation processes, after wet etching, and epitaxial Si minor carrier diffusion length, by RTPL, has been reported previously.…”
mentioning
confidence: 99%
“…Background boron (B) concentrations of the p − -Si wafers were also measured by SIMS. The background B concentration was constant at ∼1.8 × 10 15 cm −3 for all wafers. No abnormality was found from SIMS analysis.…”
mentioning
confidence: 99%